Of Ballet [Boyz] & Spectacle The choreographic world of Liv Lorent - Jackson, Paul R. W. (Dance Books Ltd., Alton,Hampshire (UK), 2006)
The choreographic world of Liv Lorent extends from Newcastle to encompass George Piper Dances Lorent's career is assessed. Lorent is one of the most musical of choreographers and what makes a visit to one of her performances so enjoyable is the range of music one hears. PALABRAS CLAVE: Liv Lorent, career, George Piper Dances, Ballet Boyz.